Challenging Native Speakerism: TEFL in Indonesia Beyond Native Speaker Fallacy - Yawan, Hendri; Marhamah (JLE: Journal of Literate of English Education Study Program, 2024)
This article examines the English native speaker fallacy and its implications in the field of Teaching English as a Foreign Language (TEFL) in Indonesia. The NS fallacy refers to the belief that Native English-Speaking Teachers (NESTs) are inherently superior and more competent in teaching English, disregarding the importance of their Pedagogical Content Knowledge (PKC). Through a synthesis research methodology, this article involves examining, integrating, and synthesizing existing conceptual and empirical studies related to teacher professional identity, NESTs, TEFL, and its implementation in Indonesia. The findings suggest that the notion of standard English taught in EFL classrooms should be questioned, as it is influenced by linguistic imperialism and marginalizes World Englishes. In Indonesia, the dominance of standardized English tests further reinforces the perception that NESTs are more competent in teaching standard English. To challenge native speakerism, the article argues for a shift in focus from linguistic proficiency to pedagogical expertise when evaluating NESTs' qualifications. Emphasizing the value of Pedagogical Content Knowledge can lead to a more inclusive and equitable hiring process, where NESTs are assessed based on their teaching capabilities and experience. By prioritizing pedagogical expertise, educational institutions can promote a culturally responsive learning environment that embraces linguistic diversity and enhances the quality of English language education in a globalized world.